"Length weight relationship of four non commercial fish species from the Southwest coast of India". (15th August 2020) - Kottappilly Surendran, Swathy; Sirajudeen Mohammed, Raffi; Thittayil, Sreenath Mohanan; Subhash, Athul
Abstract: Length weight relationships (LWRs) were estimated for four species of low value fishes that belongs to four families from the southwest coast of India. The specimens of, Callionymus margaretae, Dactyloptena peterseni, Rogadius serratus and Minous inermis were collected for a period of 1 year from the fishing trawlers of Cochin Fisheries Harbour (Lat. 09° 56′ 327″ N, Long. 76° 15′ 764″ E). The estimated allometric coefficient b values ranged from 2.5020 ( Rogadius serratus ) to 3.2438 ( Dactyloptena peterseni ) and r 2 values ranged from 0.9492 ( Rogadius serratus ) to 0.9869 ( Dactyloptena peterseni ). All the LWRs were highly significant, with p < .001.This study provides the first estimate of LWRs for these low value by catch fish species.